THE TRANSFORMATION OF ISLAMIC BOARDING SCHOOL EDUCATION IN SHAPING SANTRI’S ISLAMIC WORLDVIEW IN THE DIGITAL DISCRUPTION ERA - Hazim Rahmat Abdullah; Ngatmin Abbas; Muhammad Kurniawan Budi Wibowo (STKIP Pesisir Selatan, 2025)
This study is motivated by the limited research on the role of Islamic boarding schools (pesantren) in shaping students’ Islamic worldview in the digital disruption era, despite its significant impact on Islamic education and the moral formation of Muslim youth. The rapid advancement of technology has transformed students’ ways of thinking and behaving, requiring pesantren to adapt without losing their Islamic values. This research aims to analyze how Ma’had Tahfizhul Qur’an Baitul Hikmah Sukoharjo develops an Islamic worldview among students through curriculum design, learning methods, and the role of teachers (ustadz) amid digital challenges. This study employed a qualitative approach using a case study design, involving three main informant groups—leaders, teachers, and students—selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using Miles, Huberman, and Saldaña’s thematic analysis model, which includes data reduction, data display, and conclusion drawing. The findings reveal that education at Ma’had Tahfizhul Qur’an Baitul Hikmah plays a crucial role in constructing students’ Islamic worldview through an integrative curriculum that combines Qur’an memorization, Islamic studies, general knowledge, and character formation (adab). The ustadz serve as murabbi and muaddib, ensuring value transmission both in class and daily life.